The evaluation of psychometric properties of the Ukrainian Versions of PCL-5, PHQ-9 and GAD-7 scales - Kohut, Анна; Chaban, Олег (Psychosomatic Medicine and General Practice, 2025)
The aim of the study was to optimize the psychodiagnostic management algorithm for stress-related disorders and associated sleep disturbances by assessing the psychometric properties of the Ukrainian versions of PCL-5, PHQ-9, and GAD-7 scales. The study data included Ukrainian-language: demographic data, Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder Questionnaire-7 (GAD-7), PTSD Symptom Checklist for DSM-5 (PCL-5), Pittsburgh Sleep Quality Questionnaire (PSQQ), Toronto Alexithymia Scale (TAS-26), and Quality of Life Scale edited by Prof. Chaban (CQLS). Statistical analysis includes descriptive statistics and Pearson correlation methods, assessment of internal consistency and validity of the PCL-5, PHQ-9, and GAD-7 scales, by using SPSS Statistics 23.0. The study population (N=111) included female (76.5%) and male (23.5%) with PTSD symptoms and sleep disturbances. According to the results of the statistical analysis of the internal consistency of the scales, the Cronbach's alpha index is for PHQ-9 (0.842); GAD-7 (0.881); PCL-5 for all 20 items is: (0.954); as well as for individual subscales of symptom clusters: intrusiveness (0.891); avoidance ( .779); negative reaction ( .893); hyperreactivity ( .852). Direct strong positive, statistically significant correlation between the total score indicators for PHQ-9, GAD-7 and PCL-5 (with subscale indicators, respectively) at the level of p>0.001 ( .000), which indicates a high level of convergent validity. The results showed a high diagnostic value of using these scales in the process of diagnosing stress-related disorders with concomitant sleep disturbances.